Kesiapan Kerja: Peran Keaktifan Beroganisasi dan Efikasi Diri - Putrawan, Maldy; Suhesty, Aulia (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2024)
Unemployment is a common and complex issue across various regions in Indonesia, where good work readiness before graduation plays a key role in addressing this challenge. The high unemployment rate in Indonesia is influenced by several factors, including individual work readiness. This study aims to investigate the impact of activeness in organization and self-efficacy on the work readiness of students from the Faculty of Engineering at University X, Samarinda. A quantitative approach was used, with participants being active members of the Engineering Student, selected through simple random sampling. Data were collected using scales to measure activeness in organization, self-efficacy, and work readiness. The results show that significant effect of activeness in organization and self-efficacy on work readiness. Activeness in organization significantly influences work readiness. Self-efficacy also contributes significantly to students' work readiness. In conclusion, high activeness in organization and self-efficacy play important roles in preparing students for entering the workforce. The novelty of this study lies in examining these two variables together, offering new insights into how students' activeness in organization and self-efficacy can strengthen their readiness to face the challenges of the job market after graduation. Future research could explore other variables that contribute to work readiness and assess the long-term benefits of activeness in organization and self-efficacy using a larger sample size.